2012
DOI: 10.1097/tp.0b013e31824215db
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Human Cytomegalovirus-Specific T-Cell Response Monitoring in Predicting Viremia in Pediatric Allogeneic Stem-Cell Transplant Patients

Abstract: Given the heterogeneous scenarios of antiviral T-cell immune recovery in pediatric allogeneic HSCT, we conclude that the evaluation of the antiviral immune reconstitution is a promising and appealing system for identifying patients at higher risk of CMV infection. The use of interferon-γ ELISPOT test is a valid tool for immunological monitoring and predicting CMV viremia in pediatric HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
2
28
1
1
Order By: Relevance
“…In CMV-seronegative transplant recipients of a CMV-positive donor (D ϩ /R Ϫ ), de novo CMI develops upon primary CMV infection, which often originates from virus reactivation within the allograft, while in CMV-seropositive transplant recipients (R ϩ ), CMI recovers from previously existing immunity. The assessment of CMV-specific CMI has also been used to determine the individual risk of infection and as a helpful indicator in making therapeutic decisions, such as whether to initiate or terminate an antiviral treatment (6)(7)(8)(9)(10)(11)(12). For this reason, a diagnostic test assessing the status of immune reconstitution has been recommended in the current CMV management guidelines for transplant patients (13).…”
mentioning
confidence: 99%
“…In CMV-seronegative transplant recipients of a CMV-positive donor (D ϩ /R Ϫ ), de novo CMI develops upon primary CMV infection, which often originates from virus reactivation within the allograft, while in CMV-seropositive transplant recipients (R ϩ ), CMI recovers from previously existing immunity. The assessment of CMV-specific CMI has also been used to determine the individual risk of infection and as a helpful indicator in making therapeutic decisions, such as whether to initiate or terminate an antiviral treatment (6)(7)(8)(9)(10)(11)(12). For this reason, a diagnostic test assessing the status of immune reconstitution has been recommended in the current CMV management guidelines for transplant patients (13).…”
mentioning
confidence: 99%
“…Enzyme-linked immunosorbent spot (ELISPOT) and QuantiFERON (QFT) assays are the most standardized and employed platforms and were recently used to detect CMV-specific CMI in solid organ and allogeneic hematopoietic stem cell transplant recipients (27,28). Although their performances for CMV CMI were very similar, interassay differences were found (29,30).…”
Section: Maternal Cmv-specific T-cell Immunity As a Marker For Intraumentioning
confidence: 99%
“…ELISPOT assay results are expressed as the number of CMV pp65-specific IFN-␥ spotforming colonies (SFCs)/200,000 PBMCs. pp65 was chosen as a stimulus since it is considered to be among the major immunodominant antigens encoded by CMV (19,24,46) and has been widely used to detect CMVspecific T-cell responses in humans (1,2,7,23,41). In human trials, pp65 has also been shown to be a biologically relevant target to resolve and prevent clinically relevant infections (11,26).…”
Section: Methodsmentioning
confidence: 99%